Upaya Sekolah dalam Menanggulangi Perilaku Merokok di Kalangan Siswa SMA di Provinsi Bengkulu - Yunarman, Sepri; Akbarjono, Ali; Khermarinah, Khermarinah; Handayani, Masrifa; Wahyuningtyas, Retno; Praditya, Arga Dwi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
This study examines early smoking initiation among high school students in Bengkulu Province, Indonesia, which ranks second nationally in smoking prevalence. Early smoking often leads to long-term habits, highlighting the need for effective prevention. The research aimed to describe the profile of student smokers and analyze school-based responses in Bengkulu. A mixed-methods sequential explanatory design was used, beginning with quantitative data followed by qualitative exploration. The quantitative phase involved 117 male students in grades X–XI selected purposively, while the qualitative phase included principals, counseling teachers, and male and female student representatives. Quantitative data were analyzed descriptively, and qualitative data using Miles and Huberman’s model. Findings showed that 77% of respondents were active smokers, with 72% starting before high school. Encouragingly, 81% expressed a desire to quit. Schools have responded through student regulations, legal education, and routine inspections. The study recommends strengthening the implementation of the Smoke-Free Area Regulation (Perda KTR), including widespread dissemination, classroom signage, and regular anti-smoking campaigns. Local governments are urged to support enforcement by allocating resources and recognizing schools that actively promote smoke-free policies.